WANITA 62 TAHUN DENGAN MALNUTRISI BERAT DAN TOXIC EPIDERMAL NECROLYSIS - Yulin Arditawati; Darmono; Widyastuti (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Malnutrition and skin problems are interrelated; therefore malnutrition will reduce the function of innate and adaptive immunity. The skin contains immune cells that is crucial for host defense. A 62-year-old female patient was diagnosed with Toxic Epidermal Necrolysis (TEN) due to an unknown drug allergy and severe malnutrition. The patient has a history of inadequate intake for 1 year ago and has worsened in the last 2 weeks due to blisters all over the skin, especially in the labium oris area after taking an unknown analgetic medication. Nutrition therapy had given with a target of 1900 kcal/day gradually increased to 2200 kcal/day through enteral and parenteral with a protein of 1.5 grams/kgIBW/day. Because of patients has history of aversion to food types such as chicken, eggs, fish, cow's milk, and dairy products, so patient had given soy-based polymeric formula and Parenteral Nutrition Supplement to achieve nutrition requirement. Supplementations administered were zinc, vitamin A, vitamin B complex, and vitamin C. At the end of the treatment period there were metabolic improvement such as wound healing without secondary skin infection and improvement of albumin serum from 2,3 g/dL to 3,3 g/ dL. Patients experienced side effects due to systemic corticosteroids in the form of moon face, severe muscle wasting, hyperglycemia, and hypertension. However, the use of systemic corticosteroids should pay attention to whether the benefits outweigh the disadvantages. Keywords: toxic epidermal necrolysis, malnutrition, corticosteroid, aversion